Kadi on trial : a multifaceted analysis of the Kadi judgment - Avbelj, Matej; Fontanelli, Filippo; Martinico, Giuseppe (London : Routledge, 2014)
'The judgment of the European Court of Justice concerning the Kadi case has raised substantive and procedural issues that have caught the attention of scholars from many disciplines including EU law, constitutional law, international law and jurisprudence. This book offers a comprehensive view of the Kadi case, and explores specific issues that are anticipated to resonate beyond the immediate case from which they derive. The first part of the volume sets out an analysis of the new judgment of the Court, favouring a'contextual' reading of what is the latest link in a judicial chain. The following three parts offer interdisciplinary accounts of the decision of the European Court of Justice, including legal theory, constitutional law, and international law. The book closes with an epilogue by Ernst-Ulrich Petersmann, who studies the role of the Kadi case in the methodology of international law and its contribution to the concept of global justice. The book brings together legal scholars from a range of fields, and discusses pressing topics such as the European Union's objective of'the strict observance and the development of international law', the EU as a site of global governance, constitutional pluralism and the protections of fundamental rights'--
Introduction / Matej Avbelj, Filippo Fontanelli and Giuseppe Martinico -- Kadieu : Connecting the Dots from Resolution 1267 to Judgement C584/10P : the coming of age of judicial review / Filippo Fontanelli -- Playing Chinese Whispers : the Kadi II Decision of the General Court of the European Union / Antonella Angelini -- Thou shalt only partly judge! Jurisdictional review in the opinion of the the intervening States in Kadi II / Paolo Busco -- The case of Mr. Kadi and the Modern Concept of Law / Matej Avbelj -- Kadi in sight of autopoiesis / Jennifer Hendry -- The intractably unknowable nature of law : Kadi, Kafka and the law's competing claim to authority / Luke Mason -- The Kadi II Judgment of the Court of Justice of the European Union : Implications for Judicial Review of UN Security Council Resolutions / Arman Sarvarian -- Kadi II : backtracking from Kadi I / Nikolaos Lavranos and Mikhail Vatsov -- The Solange argument as a justification for disobeying the Security Council in the Kadi judgments / Antonios Tzanakopoulos -- Global Counter-Terrorism Sanctions and European Due Process Rules : The Dialogue Between the CJEU and the ECtHR / Federico Fabbrini and Joris Larik -- The Autonomy of EU Law : A joint celebration of Kadi II and Van Gend en Loos / Giuseppe Martinico -- Constitutional Dimensions of Administrative Cooperation : potential for reorientation in Kadi II / Nele Yang -- Multilevel judicial protection of access to justice and the EU's Duty to Contribute'to the Strict Observance and Development of International Law' / Ernst-Ulrich Petersmann.
Includes bibliographical references and index.
Keywords: El Kadi, Yasin, -- 1956- -- Trials, litigation, etc; Terrorism -- Prevention -- Law and legislation -- European Union countries -- Cases; Judicial review of administrative acts -- Law and legislation -- European Union countries -- Cases; International and municipal law -- Law and legislation -- European Union countries -- Cases